MEDICAL ILLUSTRATION IN THE COURTROOM proving injury, causation, and damages. - Coulter, Lindsay E. ([S.l.] : CRC PRESS, 2024)
Medical Illustration in the Courtroom: Proving Injury, Causation, and Damages educates the reader on how to communicate science visually--in personal injury, medical malpractice, criminal, and forensic cases--by creating art that utilizes medical records, radiographs, and computer software. Medical illustration bridges the gap between complex technical, medical, and scientific concepts to clearly illustrate, and explain visually, a medical condition, negligence, or the causation of an injury or death to the lay person. Medical artists are frequently challenged with illustrating injuries and medical conditions that can't be seen by the naked eye. And while using medical photography and imaging for illustrative purposes can be helpful, to an untrained eye it can often be unclear or confusing. This is where the medical illustrator enters the equation. There are often patients who have recovered from an injury or infection that appear in good health. However, should an unforeseen injury or fatality happen, medical illustrators can reveal to people what's actually going on inside the person, an invaluable asset to attorneys in the courtroom--especially for personal injury and medical malpractice cases. While many attorneys utilize medical artists, nonvisual people don't always recognize the value of demonstrative aids until they see them first-hand. When attorneys and their clients enlist the aid of medical artists, it quickly becomes apparent that properly conceived and executed artwork is invaluable to illustrating the facts--and medical impacts--of any number of scenarios: homicides by shooting, stabbings, vehicular accidents, in addition to medical malpractice and personal injuries resulting from surgery or possible negligence. Presenting a myriad of services and computer technologies that can be utilized, Medical Illustration in the Courtroom provides demonstrative aids used in cases to illustrate personal injury and medical malpractice, employing "tricks of the trade" to create an accurate effective image. Such images are educational to attorneys, insurance adjusters, judges, and juries to help create a visual storyline, the goal being to help combine art and science to provide a clear illustration of events to help in adjudicate legal and forensic cases.
Keywords: Medical illustration; Medical jurisprudence; ART / Techniques / General; MEDICAL / Forensic Medicine